Structural and reduced form models - Darsinos, Theo (Henry Stewart Talks, 2007)
Structural models, The Merton approach: bond pricing, stock pricing, default probability, credit spreads, bond volatility, Parameter estimation, Limitations, Extending Merton: the CreditGrades model reduced form models, Default intensity, Examples: constant, deterministic and stochastic intensities, Linking reduced and structural models, Recovery rates
Archived at 2022/04/04